Wavelet Based Optimal Control Solution for Nonlinear Systems - Hadi, Sasongko Pramono (2009)
The main objective of the research is to show the advantages of wavelet based method from conventional ones to solve a nonlinear problem in a photovoltaic solar power generation. This non linearity comes from a case of limited power of solar radiation and expensive cost of solar panel, therefore maximization of absorbed power is become important. To solve the problem, the system state space approach is used. The optimal control problem is transformed and reduced to a boundary value problem using Hamiltonian equation derivation. To increase computation speed, a wavelet analysis is used as time discretization adaptation on numerical solver that uses time discretization basis. The wavelet is employed as analysis tool at each discretization level, start from coarse to finer discretization. The temporary grid result at present level is then used for determining the next level discretization. The final results of determining maximum power, prove that optimal control scheme can be used to solve control problem of solar power generation. The computation results also show that computation speed increases significantly by employing wavelet adaptation on the conventional solver without decreasing its accuracy.